Artificial Intelligence in Higher Education: Opportunities and Challenges from the Perspective of the Information Technology Industry - Nguyen, Thi Thanh Thuy (International Journal of Advanced Multidisciplinary Research and Studies, 2025)
International Journal of Advanced Multidisciplinary Research and Studies; 5(3); pp: 841-846.